'Ethnobiological equivocation' and other misunderstandings in the interpretation of natures. (December 2020) - Furlan, Violeta; Jiménez-Escobar, N. David; Zamudio, Fernando; Medrano, Celeste
Abstract: In this contribution we seek to enrich the theoretical and methodological approaches of ethnobiology. The essay takes elements of Amerindian anthropology, classical ethnobiological studies and the freedoms provided by feminist philosophers to open up reflection. The central background of the essay is the method of "controlled equivocation" proposed by Viveiros de Castro (2004). We present a series of five ethnobiological equivocations ranging from the categorical equivocal, going through the subtle equivocal to the strictly ontological ones. The cases occurred in different territories of Argentina, including a case in an academic context. Through the fieldwork cases, we give an account of the origin of equivocations, the context for their emergence, which are the disciplinary nuances that cause them and even some academics' preconceptions. To inhabit the equivocation allows opening the possibilities of coexistence among people –and their respective worlds–, especially if these people are in different power positions. We propose the method of controlled equivocation as a theoretical-discursive tool, which permits us to rethink the current concepts of ethnobiology. Thus, we want to broaden the current definition of ethnobiology understood as a dialogue from different scientific points of view. Highlights: Controlled equivocation method is useful in ethnobiology. Epistemological equity is basic towards understanding the interpretation of natures. Ethnobiology broadens its theory and tools with ontological turn in Anthropology. Ethnobiology can promote the generation of multiple-species kinships.